A struggle to survive: The experience of awaiting pediatric heart transplantation. (4th October 2014) - Anthony, Samantha J.; Nicholas, David B.; Regehr, Cheryl; West, Lori J.
Abstract Despite the establishment of heart transplantation as a life‐saving therapy for children and adolescents, little research has focused on the biopsychosocial impact of the transplant process. Few studies have captured the subjective experiences of young heart transplant recipients. This study examined the experiences and perspectives of children and adolescents during the pretransplant phase of waiting for a donor organ. Grounded theory methods guided data collection and analysis. A total of 27 adolescents participated in semistructured qualitative interviews. Findings illuminate the waiting period for pediatric heart transplantation to be a pervasive experience, with consequent impact on physical, psychological, and social well‐being. Participants described various biopsychosocial processes and experiences that occurred during this time, with data analysis yielding themes reflecting notions of "struggling to survive, " including physical limitations, lethargy, social isolation, discomfort with physical appearance, and academic issues. This research identifies the pretransplant experience as a period framed within a text of debilitation and negative self‐perceptions related to health and well‐being. Supporting children and their families as they navigate this complex and uncertain journey is merited, and results invite further interventional development and research.